An integrated operating mechanism for lot sentencing based on process yield. Issue 2 (4th March 2022) - Liu, Shih-Wen; Wu, Chien-Wei; Wang, Zih-Huei
ABSTRACT: A flexible sampling policy integrated with the consideration of past records is discussed in this paper for the quality evaluation of submission based on process yield. Lot sentencing plays the main role in buyer-seller business contracts for deliveries. A continuous partnership between the vendor and buyer can help in maintaining historically traceable results whereby the recording information is considered valuable. Hence, we propose a new sampling strategy with an integrated operating mechanism that considers the preceding inspection results to lessen the required average sample number based on process yield. Compared with the conventional methods, the proposed modified sampling strategy has the advantage of having a small number of samples for inspection while providing desirable protection under the same quality requirements and tolerable sampling risks. An application taken from the contact lens industry is presented to demonstrate the practicability of this research.